Optimalisasi Kurikulum dan Pembelajaran Inovatif untuk Meningkatkan Mutu Layanan Pendidikan di Pondok Pesantren - Ulfa Qomariatul Jannah; Misbahul Arifin (Yayasan Literasi Altruis Khatulistiwa, 2025)
This study aims to analyze the implementation of an effective educational management system in improving the quality of educational services at Pondok Pesantren Al-Mashduqiah, with an emphasis on developing skills relevant to future demands. The CCTES (Controversy, Change, Trend, Emergency, Solution) approach was adopted in the management of pesantren education as a strategy to respond to global dynamics. Using a qualitative approach with a case study design, data were collected through interviews, observations, and documentation. The main informants included guardians, pesantren administrators, students, teachers, and educational staff. The findings show that the use of interactive textbooks with gamification features successfully reduced learning anxiety, particularly in science and language subjects. This was reflected in increased class attendance, enthusiastic participation, and improved scores on formative assessments. Furthermore, the quality of education improved in three key areas: (1) students' digital competence, as seen in their ability to use learning applications and manage online assignments; (2) critical thinking and problem-solving skills, evident through discussion activities, problem-based projects, and independent tasks; and (3) career readiness and 21st-century skills, as indicated by students’ growing confidence in facing challenges beyond the pesantren environment. The implications of this study underscore the importance of integrating technology and professional skills into pesantren education management systems as a key to producing adaptive, competent graduates who are well-prepared to meet global challenges meaningfully.